Evaluating Chris Argyris's ideas An Islamic perspective - Fontaine, Rodrigue Ancelot Harvey; Oziev, Gapur (2012)
Chris Argyris’s work touches on a fundamental point: the lack of congruence between espoused values and theories-in-use. Such incongruence is amplified by the existence of organizational defense routines. From an Islamic perspective, such an incongruence is very problematic. The paper discusses two mechanisms in the Islamic tradition – sincerity to others and mutual consultation – to overcome this problem. The case study also suggests that more modern techniques can be useful as well. The implications for management education are discussed.